Consumption of 100% Fruit Juice is Associated with Better Nutrient Intake and Diet Quality but not with Weight Status in Children: NHANES 2007-2010 - Nicklas, Theresa A.; O’Neil, Carol E.; Fulgoni, Victor L. (International Journal of Child Health and Nutrition, 2015)
Objective: This study examined the impact of various levels of 100% fruit juice (FJ) consumption on intake of nutrients, diet quality, and weight in children using the more recent national data. Methods: This was a cross-sectional study examining the data from children 2-18 years of age (n=6,090). Intake of nutrients and diet quality were assessed using the 24-hr dietary recall and Healthy Eating Index-2010, respectively. Various consumption levels of 100% FJ were determined. Covariate adjusted linear regression means, and standard errors were determined (p<0.01). Results: Average per capita consumption of 100% FJ consumed was 3.6 fl oz (50 kilocalories; 2.9% energy intake); 30% of children 2-6 years exceeded the recommendation for 100% FJ. Among 100% FJ consumers, the mean amount of 100% FJ consumed was 10.6 fl oz (147 kilocalories; 8.4% energy intake). Intakes of vitamin C, magnesium, and potassium and overall diet quality were higher with more 100% FJ consumed; no difference was found in total fiber intake. No trends were seen in weight with increased amounts of 100% FJ consumed. Conclusions: Consumption of 100% FJ should be recommended as a component of a healthy diet.